(untitled) (Research, Society and Development, 2021)
This article aims to report on the importance of the educational psychology practice in higher education. It is understood as an experience report of five interns, in a university student support program, based on records in reports and transcripts of the Psychology course interns and the field diary of the advisor by her supervision. The setting took place at a private university from northeastern Brazil, during the period from February 2020 to June 2021, from the activities developed, partly in presential and partly online, due to pandemic that devastates the world. Content analysis was applied and listed the categories: accessibility and inclusion support, psych pedagogical support, psychological listening facilitation of emotional skills workshop, the online support’s impact and the gains in psychologist’s formation. It was found that the multiple activities developed in the internship promoted gains in the training of interns and developed a new way of perceiving and accepting differences in the educational and social context.